Unintended durotomy during degenerative lumbar spine surgery (Incidence and management). - AbdulWahid, Tarik; AbdulWahid, Ali T.; Salah, Ammar (Journal of the Faculty of Medicine Baghdad, 2015)
Background: Unintended durotomy is an infrequent but well-recognized Complication during degenerative lumbar spine surgery. The current literatures report a wide variation in incidence of durotomy during degenerative lumbar spine surgery. Objective: To assess the incidence, treatment, clinical consequence, complications of unintended durotomy during degenerative lumbar spine surgery, and the results of 2-24 months clinical follow-up. Patients and Methods: A prospective study was conducted on 264 patients who underwent degenerative lumbar spine surgery performed in Al-Sheikh Zayed Hospital and private nursing home hospital- medical city in Baghdad from January 2011 to June 2012. Patients managed by spine fixation were excluded from this study. Results: The incidence of unintended durotomy during spine surgery was 8.33% (22 of 264 cases). The incidence varies according to the type of surgery being performed (6.66% in primary discectomy, 12.5% in decompressive laminectomy and 21.73% in revision surgery). Unintended durotomy was more common in revision surgery compared with primary surgery (21.73% vs 7.05%; p < .001), and it was significantly more common among elderly patients (17.39% in patients > 60 years old; p = .006). Most of the durotomies were managed by primary repair. A mean follow-up of 6 months showed good long-term clinical results. Conclusions: All unintended durotomies must be repaired primarily. Durotomies that were immediately recognized and treated did not lead to any significant sequelae at a mean follow-up of 6 months.